2019
DOI: 10.1051/e3sconf/20199302005
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Continuous Bipolar Mode Electrocoagulation (CBME) system for polishing distillery wastewater

Abstract: A continuous bipolar mode electrocoagulation (CBME) unit was used in this study for polishing a biologically treated distillery wastewater at laboratory scale. This study focuses on optimizing the process for removal of Total Organic Carbon (TOC) from an anaerobically-treated distillery wastewater. Response surface methodology (RSM) was used for optimizing the process. The study was conducted by varying three operating parameters: Initial pH (2-10), reaction time (0.5-15 min), and current density (13-40 A/sqm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Therefore, it is suggested that the current density should be limited in order to avoid the development of excessive oxygen and remove other side effects such as heat generation. 53 Similar observations were obtained by Holt et al 54 Damaraju et al 55 found that charges tend to neutralise at lower pH levels as higher metal quantities are decomposed due to higher current density, leading to floc formation and increased removal efficiency. Furthermore, this result shows that the rate of removals is enhanced when electrolysis time and stirring speed increases at the same time, which enables a longer catalytic reaction time leading to an improvement in the degradation of contaminants and a larger amount of hydroxyl radicals, which allows the production of metal-polymer complex to further improve the removal percentage.…”
Section: Statistical Analysis Optimisation and Model Validationsupporting
confidence: 70%
“…Therefore, it is suggested that the current density should be limited in order to avoid the development of excessive oxygen and remove other side effects such as heat generation. 53 Similar observations were obtained by Holt et al 54 Damaraju et al 55 found that charges tend to neutralise at lower pH levels as higher metal quantities are decomposed due to higher current density, leading to floc formation and increased removal efficiency. Furthermore, this result shows that the rate of removals is enhanced when electrolysis time and stirring speed increases at the same time, which enables a longer catalytic reaction time leading to an improvement in the degradation of contaminants and a larger amount of hydroxyl radicals, which allows the production of metal-polymer complex to further improve the removal percentage.…”
Section: Statistical Analysis Optimisation and Model Validationsupporting
confidence: 70%
“…As can be observed in Figure 4, the maximum reduction of NH 3 -N was found at a lower pH range, between 8.0 and 8.5, and zeolite dosage range of 105-110 g. This can be explained by the transformation of NH 3 -N into uncharged ammonia at higher pH (pH > 9) [49]. As a result, it would reduce the removal of NH 3 -N. As reviewed by [47], they mentioned that, at a lower pH, neutralization of charges is encouraged as higher metal amounts are dissolved owing to the greater current density, which leads to floc formation and increases in the effectiveness of removal. High removal percentages of NH 3 -N were observed at the current density peak of 600 A/m 2 and pH between 8.0 and 8.5 ( Figure 5).…”
Section: The Effects Of Factor Variables On Pollutant Removalmentioning
confidence: 80%
“…In order to validate this empirical model, several parameters were considered, such as prob < 0.05 (significant), Lack of Fit (LOF) > 0.05 (not significant), adequate precision ≥ 4, R 2 ≥ 0.8, and R 2 ≈ R 2 pre. [46,47]. Thus, according to the results shown in Table 4, justification is to be drawn that the mathematical equation of the second-order polynomial model has satisfied all the vital requirements and may be used to evaluate the effectiveness of a ZEAP treatment on the elimination of NH 3 -N pollutant.…”
Section: Analysis Of the Design Of Experimentsmentioning
confidence: 99%
“…A lack‐of‐fit test is used to evaluate the statistical model (Almeida et al, 2008). Lack‐of‐fit values for all variables were more than 0.05, indicating the nonsignificance, which proves the model was statistically significant (Damaraju et al, 2019).…”
Section: Resultsmentioning
confidence: 98%